The Evaluation of the Single-Dose Toxicity and Safety of 4-Carvomenthenol in ICR Mice - Yigun Lim; Jihoon Kong; Jiwon Lee; Gabsik Yang; Taehan Yook (MEDrang Inc., 2023)
Background: 4-carvomenthenol[4-methyl-1-(1-methylethyl)-3-cyclohexen-1-ol] is a main component of Origanum vulgare L., Zanthoxylum piperitum (L.) DC., and other plants. It has been reported to exhibit anti-inflammatory, antibacterial, and anti-tumor effects. Furthermore, it is necessary to conduct a toxicity test on 4-carvomenthenol to ensure its safety. Methods: This study included 5-week-old Institute of Cancer Research mice that were categorized into 3 treatment groups (12, 25, and 50 mg/kg 4-carvomenthenol dose levels) and a control group (10% dimethyl sulfoxide, 40% polyethylene glycol 300, 5% Tween 80, and 45% normal saline injection of the final volume), with 5 male mice and 5 female mice per group. All groups were observed for clinical symptoms and body weight in a period of 14 days and were subjected to gross necropsy after euthanasia. Results: No deaths were recorded. No test substance-related clinical signs in the female mice of the 12 mg/kg dose group were observed. Abnormal gait was observed in 1 male from day 1 to day 3 in the 12 mg/kg dose group; 1−3 males from day 1 to day 7 and 1−5 females from day 1 to day 15 in the 25 mg/kg dose group; and 2−5 males and 2-5 females from day 1 to day 15 in the 50 mg/kg dose group. No test substance-related effect on the body weight and necropsy findings was observed. Conclusion: The results of this study suggested that the lethal dose of 4-carvomenthenol could be greater than 50 mg/kg. However, further research is needed, especially repeated-dose toxicity studies, to confirm the efficacy and safety of 4-carvomenthenol.